One-pot approach for synthesis of N-doped TiO2/ZnFe2O4 hybrid as an efficient photocatalyst for degradation of aqueous organic pollutants - Yao, Y.; Qin, J.; Chen, H.; Wei, F.; Liu, X.; Wang, J.; Wang, Shaobin (Elsevier, 2015)
N-doped TiO2/ZnFe2O4 showed to be a promising catalyst and simple separation. N-doped TiO2/ZnFe2O4 catalysts were successfully prepared by coupling nitrogen modified TiO2 with ZnFe2O4 via a one-pot vapor-thermal method. The physicochemical properties of the as-prepared catalysts have been characterized using various spectroscopic and microscopic techniques. The UV-vis-light-driven photocatalytic activities of the hybrids were evaluated and the effects of the amount of photocatalyst, different types of dyes, catalyst stability on photodegradation of organic dyes were investigated. Moreover, degradation kinetics and mechanism as well as the roles of N doping, ZnFe2O4 and TiO2 have been analyzed. It was revealed that N-doped TiO2/ZnFe2O4 exhibited an improved performance compared with TiO2/ZnFe2O4 or ZnFe2O4 because of the formation of a heterostructure at the interface as well as the introduction of N species. Active species such as holes, electrons, hydroxyl radicals, and superoxide radicals involved in the photodegradation process were detected by using different types of scavengers. Because of ZnFe2O4 in the hybrid, the catalyst shows ferromagnetism, and thus, the hybrid catalyst is easily isolated from the reaction mixture after the photocatalytic experiments. This work not only offers a simple method for the fabrication of N doped TiO2/ZnFe2O4 hybrids, but also provides an effective and conveniently recyclable photocatalyst for the purification of water.